Prevalence of Plasmodium falciparum Infection among HIV Patients Attending Selected Hospitals in Niger State, Nigeria - Muhammad T. H.; Inabo, H. I.; Machido, D. A.; Ameh, J.B. (UMYU Journal of Microbiology Research)
Malaria and Acquired Immune Deficiency Syndrome (AIDS) are among the world’s greatest health problems and are concentrated in the tropical and sub-tropical regions of the world. Together, they are the cause of death of millions of people each year, hence they become a burden and a threat for development in India, Southern Asia, South America and Africa including Nigeria. The prevalence of malaria among HIV patients attending selected hospitals in Niger State, Nigeria was determined. A total of 300 HIV patients within the age range of 2-69years were enrolled, of which 217 were females and 83 were males. Four (4) mL of venous blood was drawn from each participant. The blood samples were examined for the presence of Plasmodium falciparum using thin and thick films while the CD4count was determined using flow cytometer (Partec Cyflow). Plasmodium falciparum was detected in 43 out of 300 participants with a prevalence of 14.3%.The prevalence was observed to be higher in males (18.07%) than in females (12.90%) and in the age group 1-10years (28.57%). Statistically, there was no association between Plasmodium falciparum infection with sex (p = 0.223) or age (p =0.253). The CD4 counts of all the participants ranges between 28-2000 cells/μL with a mean of 1111.40 + 739.589. Patients with Plasmodium falciparum infection had lower CD4 counts than those that were negative. Conclusively, HIV individuals with severe immunosuppression (CD4 counts <200 cells/µL) are at higher risk of Plasmodium falciparum infection. Hence, HIV individuals should take all necessary measures to prevent the infection to avoid the negative impact.